A Robust Surface-Modified Separator Fabricated with Roll-to-Roll Atomic Layer Deposition and Electrohydrodynamic Deposition Techniques for High Temperature Lithium Ion Batteries. Issue 16 (25th November 2020) - Manzoor Soomro, Afaque; Lee, Jae-Wook; Waqas, Muhammad; Kim, Young Su; Ali, Muhsin; Khalid, Muhammad Assad Ullah; Choi, Kyung Hyun
Abstract : A multilayer separator is developed by the deposition of ultrathin polyvinylidene fluoride (PVDF) and aluminum oxide (Al2 O3 ) layers on polyolefin separator using in-house designed novel roll-to-roll atmospheric atomic layer deposition (R2R-AALD) and electrohydrodynamic atomization (EHDA) methods. The conformal coatings of ultrathin PVDF (∼5 um) and Al2 O3 (∼10 nm) layers form a highly uniform interconnect microporous structure, which enhances thermal stability and mechanical strength. The deposition of PVDF and Al2 O3 layers also improves electrolyte wettability and electrolyte uptake (256%), which gives rise to ionic conductivity. The Al2 O3 /PVDF/Celgard separator shows excellent thermal stability with minimal shrinkage up to 180 °C and robust mechanical strength. The lithium cobalt oxide/graphite (LCO/graphite) cells based on as-developed multilayer separator deliver excellent discharge capacity of 130.9 mAh g −1 at 0.5 C after 150 cycles and capability of 99.6 mAh g −1 at 5 C after 100 cycles at room temperature. Moreover, the LCO/graphite cells with Al2 O3 /PVDF/Celgard separator also show remarkable cyclic performances at elevated temperatures. The as-developed separator proves to be a better candidate for high capacity lithium ion batteries, especially for high temperature conditions.